Use of Estonian Biobank data and participant recall to improve Wilson's disease management - Nurm, Miriam; Reigo, Anu; Annilo, Tarmo; Toomsoo, Toomas; Nõukas, Margit; Nikopensius, Tiit; Pankratov, Vasili; Reisberg, Tuuli; Hudjashov, Georgi; Haller, Toomas; Tõnisson, Neeme (European journal of human genetics : EJHG, 2025)
Population-based biobanks enable genomic screening to support initiatives that prevent disease onset or slow its progression and to estimate the prevalence of genetic diseases in the population. Wilson's disease (WD) is a rare genetic copper-accumulation disorder for which timely intervention is crucial, as treatment is readily available. We studied WD in the Estonian Biobank population to advance patient screening, swift diagnosis, and subsequent treatment. Combined analysis of genotype and phenotype data from electronic health records (EHRs) consolidated at the Estonian biobank led to the identification of 17 individuals at high risk of developing WD, who were recalled for further examination and deep phenotyping. All recall study participants, regardless of phenotype, age, and prior WD diagnosis, had low serum ceruloplasmin and copper levels, and 87% also exhibited signs of early to late neurodegeneration. The p.His1069Gln variant in ATP7B, a prevalent pathogenic mutation, showed a striking four- to five-fold enrichment in Estonians compared with other populations. Based on our analysis of genetic and nationwide health registry data, we estimate that WD remains underdiagnosed and undertreated in Estonia. Our study demonstrates that personalized medicine, implemented with the collaboration of medical professionals, has the potential to reduce the healthcare burden by facilitating the accurate diagnosis of rare genetic diseases. To our knowledge, this report is the first to describe a large-scale national biobank-based study of WD.